Insulin Autoimmune Syndrome: A Chinese Expert Consensus Statement - Huabing Zhang; Ming Xia Yuan; Qi Pan (Aging Medicine)
ABSTRACT Insulin autoimmune syndrome (IAS) is a rare autoimmune disorder characterized by spontaneous hypoglycemia. The incidence of IAS is higher in East Asian populations compared to other populations. Delayed diagnosis and treatment can lead to recurrent hypoglycemia, significant glucose fluctuations, and adverse clinical outcomes, including life‐threatening situations. Currently, no standardized guidelines exist for the diagnosis and treatment of IAS. This consensus aims to provide a systematic summary of the epidemiology, triggers, pathogenesis, clinical manifestations, diagnosis, differential diagnosis, treatment, and prognosis of IAS, with the objective of standardizing its clinical management.